Employer Attitudes Towards the Work Inclusion of People With Disability. Issue 6 (29th November 2013) - Nota, Laura; Santilli, Sara; Ginevra, Maria C.; Soresi, Salvatore
<x xml:space="preserve">Abstract</x> Background This study examines the importance of work in life of people with disability and then focuses on employer attitudes towards these people. In the light of Stone and Colella's model, the study examines the employer attitudes and the role of variables such as type of disability, employer experience in the hiring of persons with disabilities, the description of hypothetical hirees with disabilities, the ways in which employers evaluate work performance and social acceptability, and the work tasks that they consider appropriate for workers with disability. Method Eighty employers were randomly assigned to standard condition (candidates with disability were presented by referring to the disability they presented) or positive condition (candidates were presented with reference to their strengths). Results It was found that the type of disability and its presentation influence employer attitudes. In addition, realistic and conventional tasks were considered appropriate for hirees with disabilities. Conclusions Implications were discussed.